Efektivitas Pemberian Aromaterapi Lemon Dengan Aromaterapi Peppermint Dalam Mengurangi Emesis Gravidarum - Shinta Marlina; Riska Regia Catur Putri; Affi Zakiyya (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
Background: During pregnancy, mother experienced some discomfort. One of them that occurred in early pregnancy was the appearance of nausea symptoms and vomiting (emesis gravidarum). If they were not treated immediately, it can cause hyperemesis gravidarum. The management of nausea and vomiting can be done with complementary therapy, namely by using aromatherapy. In this study, two types of aroma therapy were used, they were lemon and peppermint aromatherapy. Objective: To determine the difference in the effectiveness of giving lemon and peppermint aromatherapy in reducing emesis gravidarum in first trimester of pregnant women. Methods: This study used a quasi-experimental method with a two-group pre-test and post-test design with a sample of 20 respondents using a simple random sampling technique. Data collection was carried out on May 20 to June 16, 2021 at Titin Widyaningsih’s MSP using the RINVR questionnaire. Results: There was a difference before and after being given lemon aromatherapy in reducing nausea and vomiting in first trimester of pregnant women with the paired t-test, the p-value was 0.001. There was a difference before and after being given peppermint aromatherapy in reducing nausea and vomiting in first trimester of pregnant women with the paired t-test, the p-value was 0.006. There was no difference between giving both aromatherapy in reducing nausea and vomiting in first trimester pregnant women with independent t-test p-value 0.738. Conclusion: There was an effect of lemon and peppermint aromatherapy in reducing emesis gravidarum in first trimester of pregnant women. There was no difference between giving both aromatherapy in reducing nausea and vomiting in first trimester of pregnant women.Keywords: Emesis Gravidarum, RINVR, lemon and peppermint aromatherapy